Hemostatic balance in patients with liver cirrhosis: Report of a consensus conference. Issue 5 (May 2016) - ,; Andriulli, Angelo; Tripodi, Armando; Angeli, Paolo; Senzolo, Marco; Primignani, Massimo; Giannini, Edoardo G.; Riggio, Oliviero; Colli, Agostino; Prati, Daniele; Sacerdoti, David; Merkel, Carlo; et al.
Abstract: Patients with cirrhosis present with hemostatic alterations secondary to reduced availability of pro-coagulant and anti-coagulant factors. The net effect of these changes is a rebalanced hemostatic system. The Italian Association of the Study of the Liver (AISF) and the Italian Society of Internal Medicine (SIMI) promoted a consensus conference on the hemostatic balance in patients with cirrhosis. The consensus process started with the review of the literature by a scientific board of experts and ended with a formal consensus meeting in Rome in December 2014. The statements were graded according to quality of evidence and strength of recommendations, and approved by an independent jury. The statements presented here highlight strengths and weaknesses of current laboratory tests to assess bleeding and thrombotic risk in cirrhotic patients, the pathophysiology of hemostatic perturbations in this condition, and outline the optimal management of bleeding and thrombosis in patients with liver cirrhosis.